REVISION OF FRENGUELLI’S (1941) PATAGONIAN ANGIOSPERM FOSSIL LEAF COLLECTION WITH COMMENTS ON THE ORIGINAL LOCALITIES (EOCENE–MIOCENE) (Ameghiniana, 2020)
Frenguelli described a fossil leaf assemblage of 36 taxonomic units (nine gymnosperms and 27 angiosperms) collected from ten localities in southwestern Patagonia. Frenguelli’s article has two limitations according to present-day standards: 1) most of the material was neither described nor illustrated; 2) the fossiliferous localities were not associated to any formal stratigraphic unit. We revised the fossiliferous outcrops and the descriptions and systematics of the angiosperm taxa of this collection. We explored the original fossiliferous localities and we included them into three formal stratigraphic units: Río Turbio, Río Guillermo, and Río Leona formations. We recognized 27 taxa: seven were assigned to known fossil-species, we kept 18 in open nomenclature and we synonymized the other two to another genus. In addition, we reported paleofloristic information of each unit: in the Río Turbio Formation the first record of the Salicaceae (Thouinia philippii?); in the Río Guillermo Formation the first record of the Grossulariaceae, Lauraceae and Salicaceae; and in the Río Leona Formation we described Nothofagus variabilis and Escalloniiyphyllum sp. for the first time.